Mites (Acari) threaten ex situ conservation actions of Ipomoea cavalcantei D.F. Austin (Convolvulaceae), an endemic species from Carajás National Forest, Pará, Brazil - Xavier, Nasly C. G.; Souza, Magno C.; Lacerda, José D. A.; Sousa, Áurea I. A. F.; Tyski, Lourival; Wurlitzer, Wesley B.; Ferla, Noeli J.; Cruz, Wilton P. (Entomological Communications, 2023)
Ipomoea cavalcantei D.F. Austin (Convolvulaceae) is a Highly Restricted Endemic species only found in Canga vegetation in conservation areas in the Carajás region, Parauapebas, State of Pará, in the Brazilian Amazon. Due to edaphic endemism and the increase in mineral exploration in the Carajás, it is necessary to cultivate I. cavalcantei outside of its habitat in order to preserve the species. On plants cultivated in a greenhouse covered with shade, at the Parauapebas Campus of the Universidade Federal Rural da Amazônia (UFRA), symptoms of pest attack were observed. The aim of this study was to characterize the damage and confirm the identification of the mite species causing injuries to the leaves of I. cavalcantei when cultivated outside its natural environment. The leaves of the plant had light green spots, which initially appeared as small dots. As the symptoms intensified, these spots coalesced, evolving into larger, yellowish spots, later necrosis and leaf fall at the slightest mechanical action. Mites were found on the abaxial surface of leaves, in abundant colonies, surrounded by a dense layer of webs, used for dispersion and oviposition of mites. This behavior, added to the shape of the eggs (spherical and hyaline) is characteristics of the mites of the genus Tetranychus Dufour, 1832 (Acari: Tetranychidae). Some female and male specimens were preserved for later identification. This is the first occurrence of Tetranychus ludeni Zacher, 1913 on I. cavalcantei and represents an important issue for conservation programs aimed at protecting I. cavalcantei.